Experimental Study of the Impact of Pore Structure on Drying Kinetics and Sublimation Front Patterns - Maximilian Thomik; Sebastian Gruber; Anders Kaestner; Petra Foerst; Evangelos Tsotsas; Nicole Vorhauer-Huget (MDPI AG, 2022)
Freeze-drying frozen maltodextrin solutions with solid contents of 5% and 30% (w/w) was experimentally investigated using neutron imaging at PSI Villigen/Switzerland. Different solid contents, as well as annealing at −5 °C for 11 h, were used to modify the porous structure of the samples, which was quantified using X-ray computed tomography. Annealing of the 5% (w/w) sample, with a pore size distribution (PSD) of 23.7 ± 11.1 µm, yielded a very open pore space with high porosity (ε = 0.96) and a PSD of 33.0 ± 27.0 µm. In contrast, the higher solid content resulted in small, lamellar, narrow pores with high anisotropy and a porosity of ε = 0.65, as well as a PSD of 13.5 ± 4 µm. In operando neutron imaging was used to show the impact of the structure of frozen maltodextrin on the overall drying kinetics and shape of the sublimation front during freeze-drying. For this purpose, a freeze-drying stage was employed, which allowed a novel approach to time- and space-resolved monitoring of the ice phase. The sublimation front propagation was quantitatively analyzed based on ice saturation profiles and sublimation rates. The dependence of drying velocity on structure is nicely demonstrated by the data. In addition, it is shown that the sublimation front widened during freeze-drying, resulting in either rather concave or convex shape depending on morphological parameters.